2022
DOI: 10.1101/2022.09.02.22279541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupted role of the connectivity between the locus coeruleus and the hippocampus in cognition of healthy, middle-aged individuals at risk of dementia: the PREVENT-Dementia study

Abstract: It is well acknowledged that Alzheimer′s Disease (AD) pathological processes start decades before clinical manifestations, but the brain mechanism of sporadic AD in midlife remains unclear. To address this gap, we examined whether risk factors for late-life AD are associated with disrupted connectivity between two key structures in AD pathophysiology — the Locus Coeruleus (LC) and hippocampus — and its role in cognition, in a cohort of middle-aged and cognitively healthy individuals. Detailed neuropsychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 113 publications
(181 reference statements)
4
20
1
Order By: Relevance
“…Known risk factors for sporadic late-onset AD (Apolipoprotein E Ɛ 4 allele status, family history of dementia, and the Cardiovascular Risk Factors Aging and Dementia score [CAIDE]) were investigated. Replicating our key previous findings (Deng et al, 2022 and Heneghan et al, 2022), we found that episodic and relational memory was (a) significantly negatively associated with the CAIDE risk score, (b) positively associated with stimulating lifestyle activities, and (c) that females performed significantly better than males in episodic and relational memory. The key novel finding of this study was that inherited dementia risk (i.e., APOE Ɛ 4 genotype) modulated the association between sex, lifestyle and cognition.…”
supporting
confidence: 87%
See 4 more Smart Citations
“…Known risk factors for sporadic late-onset AD (Apolipoprotein E Ɛ 4 allele status, family history of dementia, and the Cardiovascular Risk Factors Aging and Dementia score [CAIDE]) were investigated. Replicating our key previous findings (Deng et al, 2022 and Heneghan et al, 2022), we found that episodic and relational memory was (a) significantly negatively associated with the CAIDE risk score, (b) positively associated with stimulating lifestyle activities, and (c) that females performed significantly better than males in episodic and relational memory. The key novel finding of this study was that inherited dementia risk (i.e., APOE Ɛ 4 genotype) modulated the association between sex, lifestyle and cognition.…”
supporting
confidence: 87%
“…These findings validated the data-reduction method, in that it carved up the cognitive data into three coherent and distinct cognitive spaces – episodic and relational memory, multisensory processing, and short-term memory binding – two of which (episodic and relational memory (Bäckman et al, 2001) and short-term memory binding [Parra et al, 2016; Parra et al, 2017]) are known to be very vulnerable to early AD processes in mild cognitive impairment. The first component being the same as in Deng et al (2022), provides very strong evidence that episodic and relational memory is the top cognitive function undergoing performance variability in mid-life. The differing and stronger results here relative to Deng et al (2022) for the other two components are likely due to the larger sample (N = 461 vs N = 208) yielding higher power to detect the underlying distribution of pattern performance variability in this age group.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations